Molybdenum precursor delivery approaches in atomic layer deposition of α-MoO3. Issue 4 (12th December 2022) - Lorenzo, Daniela; Tobaldi, David Maria; Tasco, Vittorianna; Esposito, Marco; Passaseo, Adriana; Cuscunà, Massimo
Abstract : We have developed a time-saving alternative plasma enhanced atomic layer deposition process for high-quality α-MoO3 thin films which are suitable for exfoliation. Abstract : In this research work, we present a study on time-sequenced plasma-enhanced atomic layer deposition (PE-ALD) processes towards the achievement of high-quality α-MoO3 thin films which are suitable for exfoliation. In particular, a conventional precursor injection method along with a boosted precursor delivery approach are discussed and analysed. In the latter, the proposed gas supply mechanism ensures a large number of deposited Mo atoms per unit of time, which, along with a proper thermal energy, leads to high-quality and oriented orthorhombic α-MoO3 films. The proposed boosted approach is also compared with post growth annealing steps, resulting in more effective achievement of a highly oriented orthorhombic α-MoO3 phase and less time consumption.